Love’s ‘Schema and Correction’: A Queer Twist on a General Principle - Lynne Pearce (Journal of Popular Romance Studies, 2016)
In a development of my previous work on romance and repetition (see JPRS 2.1 and Ganteau and Onega 2013), this article engages W.H. Gombrich’s theory of artistic production as a process of ‘schema and correction’ in order to hypothesise why some lovers find it hard, if not impossible, to ‘live and love again’ when their relationships end. Through a close reading of Annie Proulx’s ‘Brokeback Mountain’ (1999), I explore the perceptual and cognitive mechanisms that initiate and sustain the twenty-year relationship between Ennis del Mar and Jack Twist focusing, in particular, on the ways in which the effort required to twist normative schemas of love and desire into a shape (gestalt) that accommodates homosexual attraction renders the beloved seemingly unique and irreplaceable.